“I don’t know if I can say I’m not racist”: student narratives on the history of Afro-Brazilian and indigenous culture in the Higher Education (Práxis Educativa, 2022)
The aim of this study is to analyze narratives elaborated by university students from several courses at the Universidade Regional de Blumenau on the theme of ethnic-racial diversity, from the subject “History of Afro-Brazilian and Indigenous Culture” and how it fits into the situation and in the singularities experienced by the society in question, that of the Vale do Itajaí, in Santa Catarina, Brazil. This work is anchored in debates about the construction of narratives, based on Paul Ricoeur, with the hermeneutic circle, and Jörn Rüsen, about the notion of historical learning. The sources come from a questionnaire distributed to students in the first and second academic semester of 2020. Regarding the results, this study found an important discursive re-elaboration on indigenous and Afro-Brazilian history and a recognition of the singularities of identity, contexts of denial of rights and the historical processes of exclusion.Keywords: History of Afro-Brazilian and Indigenous culture. Narratives. Historical learning.